2015
DOI: 10.1097/mao.0000000000000517
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Apoptotic Markers in HEI-OC1 Cells Treated with Gentamicin with and without the Mitochondria-Targeted Antioxidant Mitoquinone

Abstract: Mitoquinone attenuated the gentamicin-induced upregulation of the Bak gene but not its product, the proapoptotic molecule Bak, and MitoQ did not significantly decrease the gentamicin-induced cell apoptosis in vitro. Further in vivo studies are needed to assess the clinical significance of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Triphenylphosphonium has been shown to inhibit oxidative phosphorylation in vitro (36). Similarly, we found that dTPP decreased HEI-OC1 cell survival (21) and upregulated Bak gene expression (37). However, the concentrations used in vitro are typically 10 to 100 times greater than those from oral dosing; thus, the unspecific effect of dTPP is unlikely to occur with oral dosing in animal or human subjects where effective drug clearance occurs (36).…”
Section: Discussionmentioning
confidence: 86%
“…Triphenylphosphonium has been shown to inhibit oxidative phosphorylation in vitro (36). Similarly, we found that dTPP decreased HEI-OC1 cell survival (21) and upregulated Bak gene expression (37). However, the concentrations used in vitro are typically 10 to 100 times greater than those from oral dosing; thus, the unspecific effect of dTPP is unlikely to occur with oral dosing in animal or human subjects where effective drug clearance occurs (36).…”
Section: Discussionmentioning
confidence: 86%
“…A robust protective effect was observed at 500 nM concentration, and was present at D1-D3. c-Abl has been shown to be up-regulated in mouse oC following gentamicin exposure [ 34 ]. c-Src signaling has been implicated in noise-induced hearing loss, and treatment of chinchillas with Src inhibitors on the round window membrane prior to noise exposure was found to protect against HC death as measured by threshold shift and cyctocochleogram.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that suggests there is a link between antibiotic‐associated tissue damage and mitochondrial function. Aminoglycoside‐mediated ototoxicity is associated with mutations in mitochondrial DNA and changes in mitochondrial respiration, which could lead to ROS formation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%